2022
DOI: 10.1007/s10926-022-10048-5
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Opioid Use on Duration of Time Loss After Work-Related Lower Limb Injury

Abstract: Purpose This study sought to determine patterns of opioid use among workers with a compensated lower limb injury, factors associated with opioid use, and how opioid use is associated with time loss duration. Methods Claims and medication data were provided by the workers’ compensation regulator of Victoria, Australia, for claims lodged 2008–2018 from workers aged 15+ years with a lower limb injury. Descriptive statistics showed the number and prevalence of each opioid type (weak/strong) by demographic, claim a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 23 publications
(43 reference statements)
0
1
0
Order By: Relevance
“…26 Stronger opioids can also lead to a greater risk of prolonged work disability, 29 and prolonged usage is likely to cause tolerance, resulting in a stronger dose being required. 50 Therefore, the observed longer duration of time loss could be attributed to the difference in strength and volume of opioids accessed, both of which were not investigated in this study. Another potential explanation for the result is that those receiving opioids might be doing so because they are in more pain and disability.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…26 Stronger opioids can also lead to a greater risk of prolonged work disability, 29 and prolonged usage is likely to cause tolerance, resulting in a stronger dose being required. 50 Therefore, the observed longer duration of time loss could be attributed to the difference in strength and volume of opioids accessed, both of which were not investigated in this study. Another potential explanation for the result is that those receiving opioids might be doing so because they are in more pain and disability.…”
Section: Discussionmentioning
confidence: 85%
“…26 Policy features of the included workers' compensation schemes, such as the medical excess amount, were likely to have influenced the results. 36,40,50 In Victoria, employers are required to pay a medical excess up to a nominal value (approx. $700 AUD at the time of the study) before workers' compensation takes over.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One prospective and four retrospective cohort studies in people with MSDs reported either high dose, strong or long-term opioid prescriptions were associated with increased lost workdays, including a study on patients admitted to interdisciplinary functional restoration [ 66 ], employed workers with osteoarthritis [ 60 ] and WC claimants [ 65 , 74 ] and a study of workers with lower limb injury [ 63 ]. Similarly, a retrospective cohort study on persons injured with motor vehicle accident also reported early opioid prescriptions (within 10 days of accident) were a risk factor for work disability ≥ 6 months after the accident [ 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the United Kingdom, primary care physicians prescribed opioids in 59% of patients with chronic musculoskeletal pain in 2011/2012 30 . In Australia 23.6% of workers with lower limb injury claims received opioids and opioid use was associated with delayed return to work 41 . In the U.S., the prevalence of prescribed opioids in MSK conditions (back or neck problems, arthritis, rheumatism) increased by 7% from 12% in 1999/2000 to 19% in 2015/2016 42 .…”
Section: Discussionmentioning
confidence: 99%